FORMULATION DEVELOPMENT AND EVALUATION OF SUSTAINED RELEASE GASTRO-RETENTIVE FLOATING TABLETS OF AMBROXOL HYDROCHLORIDE - Mr.Prakash Singh, Dr.Arun Patel, Mr.Shailendra Patel, Dr. Adiya Sahu, Mr. Vijay Pratap Ahirwar, (EPRA International Journal of Research and Development (IJRD), 2023)
Controlled release (CR) dosage forms have been extensively used to improve therapy with several important drugs. However, the development processes are faced with several physiological difficulties such as the inability to restrain and localize the system within the desired region of the gastrointestinal tract and the highly variable nature of the gastric emptying process. Ambroxol HCl is a secretolytic agent used in the treatment of respiratory diseases associated with viscid or excessive mucus. It is the active ingredient of Mucosolvan, Mucobrox, Lasolvan, Mucoangin, Surbronc and Lysopain. The substance is a mucoactive drug with several properties including secretolytic and secretomotoric actions that restore the physiological clearance mechanisms of the respiratory tract, which play an important role in the body’s natural defence mechanisms.